Analytical and experimental investigation of cable–beam system dynamics. (October 2019) - Jalali, Mohammad Hadi; Rideout, Geoff
Interactions between cables and structures affect the design and nondestructive testing of electricity transmission lines, guyed towers, and bridges. An analytical model for an electricity pole beam–cable system is presented, which can be extended to other applications. A cantilever beam is connected to two stranded cables. The cables are modeled as tensioned Euler–Bernoulli beams, considering the sag due to self-weight. The pole is also modeled as a cantilever Euler–Bernoulli beam and the equations of motion are derived using Hamilton's principle. The model was validated with a reduced-scale system in the laboratory and a setup was designed to accurately measure the bending stiffness of the stranded cable under tension. It is concluded that the bending stiffness and sag of the cable have a significant effect on the dynamics of beam–cable structures. By adding the cable to the pole structure, some hybrid modes emerge in the eigenvalue solution of the system. Modes with antisymmetric cable motion are sag-independent and the modes with symmetric cable motion are dependent on the cable sag. The effect of sag on the natural frequencies is more significant when the bending stiffness of the cables is higher.